EFEKTIVITAS PROGRAM KAJIAN SUBUH DI MASJID MAN BA'UL ULUM DALAM MENUMBUHKAN KESADARAN BERIBADAH PADA MASYARAKAT - M. Abdul Hafiz; Egi Yekardela; Wayuk Siti Qomah; Kelin Arye Tehnisa; Ines Syafitri Rahayu; M. Zikri (PT. Hasba Edukasi Mandiri, 2026)
Religious consciousness is a fundamental aspect of Muslim life reflecting the quality of faith and devotion to Allah SWT. In the modern era filled with challenges, community religious consciousness tends to decline, particularly in the observance of congregational Fajr prayer. Man Ba'ul Ulum Mosque initiated the Subuh Study Program as a strategic effort to revive the community's spirit of worship while strengthening religious knowledge and Islamic brotherhood. This study aims to analyze the effectiveness of the Subuh Study Program at Man Ba'ul Ulum Mosque in fostering community religious consciousness, describe its implementation, identify supporting and inhibiting factors, and provide strategic recommendations. This research employs a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation. The findings indicate that the Subuh Study Program is effective in increasing congregational Fajr prayer attendance, strengthening religious understanding, and encouraging positive behavioral and social changes. Supporting factors include consistent implementation, quality of kitab-based materials, and a conducive mosque environment. Inhibiting factors include weather conditions and low participation from local RT residents. Recommendations include diversifying study content, utilizing digital technology, and strengthening synergy between mosque administrators and community leaders.